1995
DOI: 10.1002/bit.260450102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diffusion limitation on immobilized nitrifying microorganisms at low temperatures

Abstract: Activation energies of suspended and immobilized nitrifying bacteria were determined and compared to determine if diffusion limitation results in decreased sensitivity for temperature. The activation energy for the respiration activity of suspended Nitrosomonas europaea and Nitrobacter agilis was found to be 86.4 and 58.4 kJ mol(-1), respectively. The activation energy for oxygen diffusion in the support material, kappa-carrageenan, determined from the effect of temperature on the effective diffusion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…Figure 1 shows that these aggregates also contain cavities, which can develop because of the high decay rates under thermophilic conditions or during starvation periods (1). In contrast, growth of aggregates at low temperatures (10°C) results in the formation of dense and compact aggregates with a slow diffusional transport (Table 4), as has also been reported for immobilized nitrifying microorganisms (37).…”
Section: Discussionsupporting
confidence: 71%
“…Figure 1 shows that these aggregates also contain cavities, which can develop because of the high decay rates under thermophilic conditions or during starvation periods (1). In contrast, growth of aggregates at low temperatures (10°C) results in the formation of dense and compact aggregates with a slow diffusional transport (Table 4), as has also been reported for immobilized nitrifying microorganisms (37).…”
Section: Discussionsupporting
confidence: 71%
“…From these results it is concluded that the results of the Wijffels et al, 1994 model in which the separately deterined decay rates are incorporated match slightly better with the experimental data.…”
Section: Reactor Performancesupporting
confidence: 63%
“…The limiting substrate was assumed to be oxygen, and the oxygen concentration was assumed to be saturating (0.2 mol m −3 ). It was assumed that oxygen consumption took place according to zero-order kinetics and that the effective diffusion coefficient in the sponge was 2.05 × 10 −9 m 2 s −1 , which is similar to the one in gel materials we studied earlier (Wijffels et al, 1995).…”
Section: Case Studiesmentioning
confidence: 88%